Analisis Pasar Dan Referensi Konsumen Terhadap Produk Mie Sedaap - Imarananda Putri Imran; Annisa Novianti; Syamsul Hidayat (Manajemen Kreatif Jurnal, 2025)
Competition among product brands is crucial since a strong brand would discourage customers from considering making a purchase. Consumer perception of a brand is shaped by their thoughts and emotions upon hearing or seeing its name. The process of identification will enable the brand to stand out from the competition and serve as the primary factor when consumers are making judgments about what to buy. Businesses must determine which aspects of brand equity affect consumers’ confidence while making purchases.This study employed a quantitative descriptive research design. The purpose of this study was to ascertain the independent variable’s value, whether it be one or multiple variables, without doing comparisons or drawing connections between them. Quantitative descriptive research uses data in the form of numerical results from measurements to characterize variables as they actually exist. One of the things that might persuade people to buy instant noodle products is brand recognition. The majority of consumers who claim that they opt to purchase instant noodles due to their well-known brand demonstrate this beneficial impact. Customers think that their assessment of a product’s quality will assist them decide which one to purchase.